Comparison of Baumgaertner and Chang reduction quality criteria for the assessment of trochanteric fractures. Issue 10 (October 2019) - Mao, Wei; Ni, Haofei; Li, Linli; He, Yiqun; Chen, Xujun; Tang, Han; Dong, Youhai
Abstract : Objectives: Different criteria for assessing the reduction quality of trochanteric fractures have been reported. The Baumgaertner reduction quality criteria (BRQC) are relatively common and the Chang reduction quality criteria (CRQC) are relatively new. The objectives of the current study were to compare the reliability of the BRQC and CRQC in predicting mechanical complications and to investigate the clinical implications of the CRQC. Methods: A total of 168 patients were assessed in a retrospective observational study. Clinical information including age, sex, fracture side, American Society of Anesthesiologists (ASA) classification, tip-apex distance (TAD), fracture classification, reduction quality, blade position, BRQC, CRQC, bone quality, and the occurrence of mechanical complications were used in the statistical analysis. Results: A total of 127 patients were included in the full analysis, and mechanical complications were observed in 26 patients. The TAD, blade position, BRQC and CRQC were significantly associated with mechanical complications in the univariate analysis. Only the TAD (p = 0.025) and the CRQC (p < 0.001) showed significant results in the multivariate analysis. In the comparison of the receiver operating characteristic curves, the CRQC also performed better than the BRQC. Conclusion: The CRQC are reliable in predicting mechanical complications and are more reliable than the BRQC. Future studies could use the CRQC to assess fracture reduction quality. Intraoperatively, the surgeon should refer to the CRQC to achieve good reduction in trochanteric fractures. Cite this article : Bone Joint Res 2019;8:502–508. DOI: 10.1302/2046-3758.810.BJR-2019-0032.R1.